Philippine mycology II: an integrative taxonomic classification of novel Basidiomycota, basal fungi, and fungus-like phyla from the Philippines - Opiña, Lilcah Angelique; Bagacay, Jan Felnesh Exe; Siccio, Majoerly Augustine; Sara, Fred Ric; Canto, Carr Marlo; Silaras, Mark Leonard; Ynion, Gene Philip Levee Q.; Calabon, Mark S. (Phytotaxa, 2026)
The Philippines possesses significant fungal diversity, although comprehensive taxonomic assessments remain scarce. This study presents an overview of novel Basidiomycota, basal fungi, and fungus-like taxa identified in the Philippines, based on an extensive review of published records from fungal repositories. A total of 412 Basidiomycota species have been documented, encompassing 24 genera, 65 families, 24 orders, and 7 classes (Agaricomycetes, Dacrymycetes, Exobasidiomycetes, Microbotryomycetes, Pucciniomycetes, Tremellomycetes, Ustilaginomycetes). Additionally, four phyla of basal fungi were recorded: Basidiobolomycota (2 species, 2 genera, 1 order, 1 class), Chytridiomycota (3 species, 3 genera, 3 families, 2 orders, 1 class), Entomophthoromycota (5 species, 4 genera, 1 order, 1 class), and Mucoromycota (1 species from a single genus, family, order, and class). The fungi-like phylum Oomycota (Kingdom Chromista) was also represented, with 8 species, 6 genera, 3 families, 2 orders, and 1 class. This compilation extends previous efforts to update the status of mycology in the Philippines and provides valuable insights into the country’s fungal biodiversity. The results underscore the rich mycological diversity of the Philippines and reinforce the necessity for ongoing taxonomic research, biodiversity documentation, and conservation initiatives.